Using Medicine to Explain Meteorological Principles. Remarks on Two Parisian Question Commentaries on the Meteorologica of Aristotle - Marcon, Chiara (Bulletin de Philosophie Médiévale, 2024)
Abstract From Hippocrates and Galen, meteorological medicine studied the impact of environmental factors and weather phenomena on mental and bodily health. This theory has been largely diffused by medical works and encyclopaedias, such as those of Vincentius de Beauvais and Bartholomeus Anglicus. However, its reception within mediaeval meteorology still remains to be fully inquired, partly because it was not a traditional topic to be discussed in the question commentaries on the Meteorologica of Aristotle. This article aims to focus on three Parisian quaestiones on the Meteorologica in which Radulphus Brito and Themo Iudaei de Monasterio utilised concepts of meteorological medicine as a tool to explain meteorological principles. The medical theory is used to clarify how antiperistasis works within animals’ bellies and its impacts on their general health; and in the second one, to describe the harmful impacts water has on human and animal bodies; and then thirdly, to explain the process of generating rain.